THE INFLUENCE OF WORK DISCIPLINE, WORK MOTIVATION AND WORK ENVIRONMENT ON EMPLOYEE PERFORMANCE: PENGARUH DISIPLIN KERJA, MOTIVASI KERJA DAN LINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI - Bhayangkara, Kurnia Resky; Idris, Idris; Hasanudin, Bakri (Master of Management Study Program, Faculty of Economics and Business, Tadulako University, 2023)
The purpose of this study was to determine the effect of work discipline, work motivation, and work environment on the performance of Pasangkayu Regency Bappeda Litbang employees. The subjects of this research were all employees of Bappeda Litbang Pasangkayu Regency. The research method used is quantitative method with descriptive verification research type. The sampling technique used in this study was the census technique using multiple linear regression analysis methods. Data collection was done directly by distributing questionnaires to respondents as many as 34 employees of Bappeda Litbang Pasangkayu Regency. The results showed that the variables of motivation discipline and work environment simultaneously had a significant effect on the performance of employees of Bappeda Litbang Pasangkayu Regency. Partially discipline, motivation and work environment also have a significant effect on employee performance at Bappeda Litbang Pasangkayu Regency.